Akuntansi Forensik di Era Digital: Sintesis Sistematis atas Integrasi Big Data, AI, dan Kerangka Analitik dalam Deteksi Kecurangan (2016–2025) - Winda Wulandari; Retna Sari; Heksawan Rahmadi; Wieldy Menanda; Dwi Prastowo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study synthesizes the development of forensic accounting research in the digital era from 2016 to 2025 using a Systematic Literature Review (SLR) guided by the PRISMA protocol. Twenty-six Scopus-indexed articles were analyzed through the Theory Context Methodology (TCM) framework to map theoretical, methodological, and contextual trends. Findings indicate that the Fraud Triangle Theory remains the dominant foundation but is increasingly integrated with Technology Organization Environment (TOE) and Resource-Based View (RBV) frameworks to explain technological adoption and organizational capability in digital forensic auditing. Thematic analysis identifies five key directions: behavioral fraud theory, AI-based digitalization, ethical governance, organizational capability, and methodological innovation. This study introduces the Forensic Accounting 4R Model (Regulation Risk Response Reinforcement), emphasizing synergy among technology, ethics, and governance in strengthening fraud prevention. Theoretically, it unifies behavioral, technological, and ethical dimensions in one conceptual framework, while practically offering insights for improving digital governance and forensic audit competence in emerging economies.